Chronic hypoxia disrupts T regulatory cell phenotype contributing to the emergence of exTreg-TH17 cells - Lantz, Benjamin J.; Moriwaki, Mika; Oyebamiji, Olufunmilola M.; Guo, Yan; Gonzalez Bosc, Laura (Frontiers in Physiology, 2024)
The imbalance between proinflammatory T helper 17 (TH17) cells and anti-inflammatory regulatory T cells (Tregs) has been implicated in multiple inflammatory and autoimmune conditions, but the effects of chronic hypoxia (CH) on this balance have yet to be explored. CH-exposed mice have increased prevalence of TH17 cells in the lungs with no change in Tregs. This imbalance is significant because it precedes the development of pulmonary hypertension (PH), and TH17 cells have been shown to be a major contributor in CH-induced PH. While Tregs have been shown to attenuate or prevent the development of certain types of PH through activation and adoptive transfer experiments, why Tregs remain unable to prevent disease progression naturally, specifically in CH-induced PH, remains unclear. Our study aimed to test the hypothesis that increased TH17 cells observed following CH are caused by decreased circulating levels of Tregs, and switching of Tregs to exTreg-TH17 cells following CH. We compared gene expression profiles of Tregs from normoxia or 5-day CH splenocytes harvested from Foxp3tm9(EGFP/cre/ERT2)Ayr/J x Ai14-tdTomato mice, which allowed for Treg lineage tracing through the presence or absence of EGFP and/or tdTomato expression. We found Tregs in CH exposed mice contained gene profiles consistent with decreased suppressive ability. We determined cell prevalence and expression of CD25 and OX40, proteins critical for Treg function, in splenocytes from Foxp3tm9(EGFP/cre/ERT2)Ayr/J x Ai14-tdTomato mice under the same conditions. We found TH17 cells to be increased and Tregs to be decreased following CH, with protein expression of CD25 and OX40 in Tregs matching the gene expression data. Finally, using the lineaging tracing ability of this mouse model, we were able to demonstrate the emergence of exTreg-TH17 cells following CH. These findings suggest CH causes a decrease in Treg suppressive capacity, and exTregs respond to CH by transitioning to TH17 cells, both of which tilt the Treg-TH17 cell balance towards TH17 cells, creating a proinflammatory environment.